Karakteristik Tafsir Nusantara: Studi terhadap Metode Tafsir Juz ‘Amma Karya Firanda Andirja (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This research was motivated by the presence of a book of Tafsir Juz Amma in 2018. This interpretation was written by Ustadz Firanda Andirja whom is an Indonesian preacher whose educational background is non-tafsir. This book was written for several reasons, including many Muslims who are passionate about studying the Qur’an in terms of the laws of Tajwid. But few have studied its contents, while the main purpose of the Al-Quran is to be practiced and not just read. For this reason, this study aims to determine the characteristics of Firanda Andirja's Tafsir Juz Amma method and its advantages and disadvantages. This research is a library research study with the primary source being Firanda Andirja's Tafsir Juz Amma, and secondary sources, Firanda Andirja's journals and videos that are relevant to this research. The approach of this research is content analysis. The results showed that the method applied in Firanda's Tafsir Juz Amma is the semi-tahlili method. This can be seen from the way Firanda interprets the verse with a fairly long explanation and displays various sources and various comments on the verse, but in terms of the content of the explanation it is not too detailed. The advantages of Tafsir Juz Amma by Firanda, among others, are that there are pictures and colors that spoil the eyes of the reader and easy to read, the contents of the interpretation are easy to understand, the selected hadith can be trusted to be authentic, free from israiliyat, while the drawback is that it cannot provide a detailed understanding, in mentioning some of Firanda's narrations, he rarely commented on these narrations and the pictures listed were not given any description.